Plasma miR-451 with echocardiography serves as a diagnostic reference for pulmonary hypertension - SONG Xiao-wei; ZOU Lu-lu; CUI Ling; LI Song-hua; QIN Yong-wen; ZHAO Xian-xian; JING Qing (Acta Pharmacologica Sinica, 2018)
Due to the lack of typical clinical symptoms, the average delay time for diagnosis of pulmonary hypertension (PH) is longer than 2 years. It is urgent to find biomarkers for PH diagnosis. In this study we investigated whether plasma microRNAs (miRNAs) can be used as biomarkers for PH diagnosis. We used microarray to identify dynamic miRNAs between PH and non-PH patients. The candidate miRNAs were verified using qRT-PCR in a mouse model of PH, which was induced by monocrotaline (MCT) injection. We observed that miR-21, miR-126, miR-145, miR-191 and miR-150 had no differences between control mice and MCT-treated mice; but plasma miR-451 was significantly decreased in the 2 wk-MCT group, with no further decrease in the 4 wk-MCT group. Plasma miR-451 was also markedly decreased in PH patients, whereas miR-21, miR-126, miR-150 and miR-320 did not show differences between 53 PH patients and 54 non-PH patients.